Strategi Pemasaran Pelayanan Home Care Rumah Sakit Umum Bhakti Rahayu Denpasar - Suwedia, I Nyoman Gede Bayu Wiratama; Daruki, Maria Wahyu (UI Scholars Hub, 2019)
Changes in the pattern of diseases to degenerative diseases and chronic diseases are growing lately and many hospitals have not yet developed chronic disease services. Bhakti Rahayu General Hospital has one of them Home Care (HC) services that has been running but has not developed well due to the lack of marketing to patients with categories and diagnoses of diseases that can be treated with HC, so it is necessary to develop and plan strategies in marketing home care services as one of the hospital's earnings. This study was conducted using a pattern of observation and participation; in-depth interviews with home care officers, patients and directors. Based on the results of the study, information was obtained that the opportunities and potential for developing HC with a pattern of determining the right strategy can lead to good direction as one of the income posts for the hospital by prioritizing patient satisfaction so that the patient's desire to pay can occur and the patient feels comfortable with the service provided. given an ongoing quality of service and improved skills and product improvements offered and the appropriate price can be a pretty good bargaining value. So, it can be concluded that the prospect of developing HC services in Bhakti Rahayu General Hospital is quite large. Alternative marketing strategies for visiting and hospitalized patients and offering through social media can be a strong enough point in marketing the products offered.